The Influence of Resource Based View and Business Performance on Business Competitiveness (Case Study at PT. JAS Mulia, North Luwu Regency) - Andi Nadirah Mahmud; Ilham Tahier; Yonerius Yonerius (Jurnal Mantik, 2022)
Research aims to determine the effect of Resource Based View and Business Performance on Business Competitiveness in North Luwu Regency. The population in this study the population is employees of PT. JAS Mulia, which has 200 employees. The number of samples in this study by calculating using the Slovin formula, then obtained a sample of 133 employees . The data analysis method used is multiple linear regression. The results showed that the Resource Based View does not have a positive effect on business competitiveness, while business performance has a positive effect on business competitiveness